2022
DOI: 10.3389/fpls.2022.849553
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Melatonin Alleviates Alkaline Stress by Removing Reactive Oxygen Species and Promoting Antioxidant Defence in Rice Seedlings

Abstract: Saline-alkali stress seriously restricts rice growth, development, and production in northern China. The damage of alkaline stress on rice is much greater than that of salt due to ion toxicity, osmotic stress, and especially high pH. As a signal molecule, melatonin (N-acetyl-5-methoxytryptamine, MT) mediates many physiological processes in rice and participates in protecting rice from abiotic stress. The potential mechanism of exogenous melatonin-mediated alkaline stress tolerance is still largely unknown. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 77 publications
3
26
1
Order By: Relevance
“…This study showed that exogenous melatonin dramatically upregulated the expression levels of the ALM1 , OsPOX , OsCATC , and OsAPX2 genes, improving the activities of the antioxidant enzymes CAT, SOD, POD, and APX, respectively. Consequently, exogenous melatonin relieved drought stress in rice seedlings by primarily strengthening enzymatic antioxidant systems rather than non-enzymatic antioxidants (AsA and DHA), which was somewhat different from our earlier research on the physiological mechanisms of exogenous melatonin alleviating alkaline stress tolerance in rice [ 38 ].…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…This study showed that exogenous melatonin dramatically upregulated the expression levels of the ALM1 , OsPOX , OsCATC , and OsAPX2 genes, improving the activities of the antioxidant enzymes CAT, SOD, POD, and APX, respectively. Consequently, exogenous melatonin relieved drought stress in rice seedlings by primarily strengthening enzymatic antioxidant systems rather than non-enzymatic antioxidants (AsA and DHA), which was somewhat different from our earlier research on the physiological mechanisms of exogenous melatonin alleviating alkaline stress tolerance in rice [ 38 ].…”
Section: Discussioncontrasting
confidence: 70%
“…A previous report showed that under salt stress, the application of 20 μM melatonin might accelerate the accumulation of osmotic compounds (such as proline and soluble sugars) in cotton seeds, improving the tolerance of seed germination to salt stress [ 41 ]. Our previous study indicated that exogenous melatonin increased the proline content while decreasing the sucrose and fructose levels in alkaline-stressed rice seedlings, which suggested that exogenous melatonin improved the alkaline tolerance by accumulating proline rather than sucrose and fructose in rice [ 38 ]. In the presented study, the application of exogenous melatonin increased the proline accumulation by activating OsP5CS gene expression and increasing the sucrose and fructose contents by upregulating the expression levels of the OsSUS7 and OsSPS1 genes in rice seedling leaves under drought stress.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, melatonin priming promoted seed germination by regulating the expression of stress tolerance, hormone synthesis, and metabolism-related genes . On the other hand, priming treatment also upregulated the antioxidant enzyme activities and accelerated the level of reserve mobilization, ultimately improving the seed germination (Arora and Bhatla, 2017;Cao et al, 2019;Lu et al, 2022). This study is the first to reveal the effect pathways of melatonin priming on the S. corniculata seed germination under salinization stress, and also proved the feasibility of melatonin priming in improving the germination of S. corniculata seeds.…”
Section: Pathways Of Melatonin Priming In Suaeda Corniculata Seed Ger...supporting
confidence: 53%
“…Exogenous melatonin priming may have indirectly upregulated the expression of antioxidant enzyme and related genes, which then improves their efficiency as antioxidants (Arora and Bhatla, 2017;Wang et al, 2017). However, other studies have demonstrated that exogenous melatonin priming did not change the antioxidant enzymes' activity of Lolium perenne (Zhang et al, 2016;Lu et al, 2022), and we suspect that melatonin possibly uses different physiological mechanisms to strengthen the antioxidant defense. MDA is the indicator of oxidative-stress induced membrane damage under salinization stress (Ibrahim, 2016).…”
Section: Effect Of Melatonin Priming On Antioxidant Defense Of Suaeda...mentioning
confidence: 81%
“…Melatonin is the most powerful endogenous free radical scavenger. Its main antioxidant mechanism acts through its binding to oxidative substances (Lu et al, 2022). Additionally, melatonin binds to its cellular receptor and activates the transduction signals that induce the synthesis of antioxidant enzymes, including superoxide dismutase, catalase, glutathione peroxidase, and glutathione reductase (Bantounou et al, 2022).…”
Section: Effect and Molecular Mechanismmentioning
confidence: 99%